Influence of perceived leadership style and emotional intelligence on employees innovative work behavior in selected SMEs of Tehran, Iran - Latifi, Marjan (2022)
Globalization has obliged developing countries’ SMEs to foreign competition and to survive and become competitive in local and global markets; innovation is a critical factor for SMEs which play a key role in the economy of countries around the world. After reviewing the literature of previous Iranian studies, most of them unanimously agreed that "the lack of innovation" was the main reason for making Iranian SMEs uncompetitive in both the local and the international markets. Therefore, to foster a high rate of innovation within the organization, employees should be encouraged to adopt innovative work behavior (IWB). Since one of the most important causes of business failure in the Iranian context is mismanagement, this study aims to investigate the influence of perceived leadership style and emotional intelligence of employees on their innovative work behavior and its dimensions (idea generation, idea promotion, idea realization), among 195 employees from selected SMEs in the capital city of Iran, "Tehran". The correlation quantitative research was applied through three instruments to define the research objectives including MLQ5x (Bass & Avolio, 2004), SSEIT (Schutte, 1998), and IWB (Janssen, 2000) after being translated from English to Persian and testing the validity and reliability. To determine the appropriate sample size, GPower 3.1 statistical software was used and stratified random sampling was applied. Both descriptive and inferential statistics were used as analytical tools. The transformational leadership style and innovative work behavior of employees were correlated and significantly positive while the correlation between transactional leadership and employees' innovative work behavior was significant but weak. The findings have shown that emotional intelligence was related and had a positive impact on innovative work behavior and its subscales. Stepwise Regression Analysis has shown that emotional intelligence, transformational, laissez-faire leadership style, and the level of education significantly predicted innovative work behavior and its components. Also, idea generation was significantly associated with the laissez-faire leadership style, while transactional was not. This study developed a model that states situational leadership style based on Full Range Leadership Model and emotional intelligence both would be predictive factors for innovative work behavior. Social Exchange Theory which has been considered the underpinning theory matched the model. Contributing the findings to the HRD field might be a turning point in this domain for filling the gap in theory and practice that seems its important implications, especially for SME entrepreneurs and scholars.